2017
DOI: 10.19084/rca16021
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do quitosano e ácido acético na conservação de uva de mesa

Abstract: R E S U M OTodos os frutos sofrem perdas de qualidade desde o momento da colheita até ao seu consumo. A utilização de quitosano como revestimento edível tem sido uma alternativa no tratamento pós-colheita de uva de mesa com bons resultados. Tendo em consideração que a preparação de revestimentos à base deste biopolímero é realizada em solução de ácido acético, pretendeu-se avaliar se a aplicação do referido ácido terá alguma influência nas características físico-químicas da uva de mesa durante o período de con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In recent years, there has been a growing interest in the use of innovative and environmentally friendly technologies, such as edible coatings or films and biodegradable films associated with the application of natural compounds, like essential oils, that will both add value to food products and extend their shelf-life [75][76][77].…”
Section: Magnifying Glass Observation Of Penicillium Spp On a 'Crimson' Table Grape Berry Using An Olympus Sz61 At 350x Magnificationmentioning
confidence: 99%
“…In recent years, there has been a growing interest in the use of innovative and environmentally friendly technologies, such as edible coatings or films and biodegradable films associated with the application of natural compounds, like essential oils, that will both add value to food products and extend their shelf-life [75][76][77].…”
Section: Magnifying Glass Observation Of Penicillium Spp On a 'Crimson' Table Grape Berry Using An Olympus Sz61 At 350x Magnificationmentioning
confidence: 99%
“…The use of chitosan with antimicrobial efficiency in food products is commonly observed in the form of coatings, with a small number of studies that use it as a direct ingredient in the food matrix (ASSIS; BRITTO, 2014;GOL et al, 2015;ARAÚJO;SHIRAI, 2016;CHEVALIER et al, 2016;RICARDO-RODRIGUES et al, 2017). Barros, D. M. et al The survival curve of S. aureus in coalho cheese with chitosan as a coating (Table 2), showed that treatments T2 (10 mg mL -1 chitosan) and T3 (15 mg mL -1 chitosan) had similar results with logarithmic microbial reductions ranging from 0.69 to 3.00 and 0.92 to 3.04, respectively, in relation to the control, considering all the time intervals evaluated (Table 2).…”
Section: Viability Of S Aureus Versus Chitosan In Coalho Cheesementioning
confidence: 99%